From Isolation to Interaction: The Role of Language and Digital Communication Tools in Empowering Adolescent Virtual Collaboration - Shazia Hamid; Anthonia Awhinawhi (Language, Technology, and Social Media, 2025)
This qualitative study explores the impact of collaborative learning on adolescent learners' motivation and feelings of isolation in virtual learning environments, with a focus on the role of language-mediated interactions and digital tools. Using exploratory questionnaires and interviews, the study examines how virtual collaborative tasks influence students' engagement. The findings indicate that collaborative learning significantly enhances motivation, particularly when tasks are meaningful and peer interactions are supportive. Survey data revealed that 42.4% of students often found collaborative tasks productive, with positive peer influence acting as a key motivator. Additionally, 70% of participants reported a reduction in isolation due to peer interaction. Autonomy in collaborative tasks was also strongly linked to higher intrinsic motivation, supporting Self-Determination Theory. Synchronous tools such as video conferencing and shared documents were crucial in alleviating isolation. The study highlights how digital tools mediate language use, fostering social connection and engagement in virtual settings. It contributes new insights into the integration of digital tools for language learning, collaboration, and social engagement, offering practical recommendations for virtual education practices, curriculum design, and teacher training, with implications for policymakers to enhance online learning strategies.